(untitled) (Fiep Bulletin - online, 2015)
Introduction: The critical power and velocity are basic concepts to study fadigue and exhaustion in not resisted dynamic exercises. However there isn´ t so much knowledge about the behavior of the exercise in the critical force intensity. Objective: The aim fo this study was to determine the critical force intensity and the number of repetitions made until the exhaustion of it. Method: Twelve masculine volunteers with average age of 22,21 ± 2,48;and 78,58±8,78 weight.They did four tests until voluntary exhaustion on leg press 45º machine. The three first tests had been done variedly beteween 80, 50 and 20% 1RM intensities, and had been used to determinate the critical force by exponential equation. After determination of corresponding critical force intensity, the voluntaries did a last test until exhaustion. Blood Samples (25ul) had been collected in rest and five minutes after the accomplishment of each test, for lactatemia determination. Results: The values of the maximum number of repetitions for each maximum load intensity were 14,78 ±5,78 for 80% 1RM; 39,44 ±11,63 for 50% and 206,11 ±136,63 for 20% 1RM. The number of maximal repetitions done in the critical force intensity were 406,27±339,51. The values of lactatemia were 7,48±2,78; 9,03± 2,59; 6,22 ± 2,92 and 2,65 ± 1,24 respectively for 80, 50, 20 and 18.11% (critical force) 1RM. Conclusion: Through these results we can conclude that the critical force value is smaller than lactate threshold intensity in resistence exercise, promoting raised number of repetiton until exhaustion. However for being a physiological phenomenon and not mathematician, the fatigue still is evident.